ANTIBIOGRAM AND SUSCEPTIBILITY PATTERN OF METHICILLIN-RESISTANT STAPHYLOCOCCUS AUREUS COLLECTED FROM VARIOUS CLINICAL SAMPLES IN BENGALURU - Debnath, Anamika; Chikkaswamy, Budiguppe Kapanigowda (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Methicillin-resistant Staphylococcus aureus (MRSA) is a major cause of nosocomial and community infections. A total of 671 clinical specimens were collected and subjected to standard microbiological screening methods for S. aureus. Subsequently, the antibiotic sensitivity test was performed for the confirmed MRSA isolates. Out of 323 (48.14%) strains of S. aureus isolated from clinical samples, 97 (30%) were found to be MRSA. The prevalence rate of MRSA was higher in clinical samples collected from males (58.8%) when compared to MRSA strains isolated from samples collected from females (41.2%). The highest number of MRSA isolates of 78.4% of MRSA strains were obtained from wound pus samples, 3.1% from urine, 4.1% from sputum, 5.2% from eye swab, and 1.0% from ear swab. The percentage of MRSA stains isolated among the age group 21-30 years is 3.5-fold higher than the strains isolated from the group aged between 61 and 70 years (6.19%). Almost all clinical MRSA strains (100%) were resistant to oxacillin, 90% resistant to ampicillin, 84.5% to penicillin-G, 76.2% erythromycin, 71% to cephalexin, and 40.2% to cotrimoxazole. However, here we reported 7.22% MRSA strains resistance to linezolid and 28.87% to vancomycin. The higher percentage of intermediate resistance was noted against antibiotics such as gentamycin and ciprofloxacin. Keywords: Staphylococcus aureus, Methicillin resistance, Nosocomial infections, Vancomycin, Linezolid.